(untitled) (The Pakistan Development Review, 2013)
Friedrich List was a German-American economist who considered economics a science of politics and culture. As a modernist, he promoted an urban-industrial society, through gradual and pragmatic policies. He had considerable impact on a geopolitical scale, and his theories contributed to significant changes in the international balance of powers. For a good reason, the textbooks of mainstream Anglo-American economics weeded out the German-American economist Friedrich List (1789-1846). Why? Because List gave away the family secret. List described its details, reasons and logic. The treasure to be kept secret was, and is, the strategy to accumulate national wealth and power. List has thus been characterised as: